Import and Export of Misfolded α-Synuclein - Rodriguez, Lilia; Marano, Maria M.; Tandon, Anurag (Frontiers in Neuroscience, 2018)
In Parkinson's disease, intracellular -synuclein (-syn) inclusions form in neurons and are referred to as Lewy bodies. These aggregates spread through the brain following a specific pattern leading to the hypothesis that neuron-to-neuron transfer is critical for the propagation of Lewy body pathology. Here we review recent studies employing pre-formed fibrils generated from recombinant -syn to evaluate the uptake, trafficking, and release of -syn fibrils. We outline methods of internalization as well as cell surface receptors that have been described in the literature as regulating -syn fibril uptake. Pharmacological and genetic studies indicate endocytosis is the primary method of -syn internalization. Once -syn fibrils have crossed the plasma membrane they are typically trafficked through the endo-lysosomal system with autophagy acting as the dominant method of -syn clearance. Interestingly, both chaperone-mediated autophagy and macroautophagy have been implicated in the degradation of -syn, although it remains unclear which system is chiefly responsible for the removal of -syn fibrils. The major hallmark of -syn spreading is the templating of misfolded properties onto healthy protein resulting in a conformational change; we summarize the evidence indicating misfolded -syn can seed endogenous -syn to form new aggregates. Finally, recent studies demonstrate that cells release misfolded and aggregated -syn and that these processes may involve different chaperones. Nonetheless, the exact mechanism for the release of fibrillar -syn remains unclear. This review highlights what is known, and what requires further clarification, regarding each step of -syn transmission.